Pengaruh Kemudahan Penggunaan, Manfaat dan Risiko Terhadap Keputusan Penggunaan QRIS pada Mahasiswa UNISRI Surakarta - Mayang Segari; Marjam Desma Rahadhini (Teewan Journal Solutions, 2025)
QRIS as a digital transaction tool emerged in response to technological developments and the need to increase efficiency and inclusiveness in the payment system. Along with technological advances and digitalization trends, the use of digital payments is increasing. QRIS facilitates digital transactions in a fast and efficient way, allowing payments through QR code scanning without cash or cards. The advantages include convenience, security, and financial inclusion, although there is a risk of personal data leakage and misuse of transactions if users are not careful. This study is a quantitative study that examines the influence of ease of use, benefits, and risks on the decision to use QRIS, using survey methods and primary data from questionnaires given to UNISRI Surakarta students. Sampling technique using proportional stratified random sampling technique is used to calculate the proportion of the number of samples in a non-homogeneous and stratified population, so that the number of samples becomes proportional based on the grouping of students as many as 100 respondents. Instrument testing is carried out through validity and reliability tests. In addition, a classical assumption test is carried out which includes multicollinearity, autocorrelation, heteroscedasticity, and normality tests. Data analysis was carried out using descriptive analysis, multiple linear regression with moderating variables, as well as t-test, F-test, R2 test, and moderation test. The results of the study indicate that 1) ease of use has been shown to have a significant influence on the decision to use QRIS among UNISRI Surakarta students. 2) The benefits of using QRIS have been shown to have a significant influence on the decision to use QRIS among UNISRI Surakarta students. 3) The risk of using QRIS has been shown to have a significant influence on the decision to use QRIS among UNISRI Surakarta students.